2019
DOI: 10.1002/jum.15062
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound‐Guided Biceps Tendon Sheath Injection: Spectrum of Preprocedure Appearances

Abstract: Objectives-To determine the frequency of ultrasound (US) appearances of the extra-articular long head of the proximal biceps tendon in patients referred for US-guided biceps tendon sheath injections.Methods-We reviewed our US-guided biceps tendon sheath injections between January 2015 and December 2017, noting the appearance of the biceps tendon and sheath, as well as the needle size used, and what was injected. Clinical electronic medical records were also reviewed to determine safety and patients' responses.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…이 경우 전체 바늘의 위치를 시각화 하면서 관찰할 수 있으며, Out-of-plane의 경우 탐촉 자의 장축 방향과 바늘이 수직 방향이기에 바늘이 단면, 즉 점 (Dot)으로 보이게 된다 48) . 때문에 In-plane approach의 경우 바늘의 시각화에는 장점이 있지만, 목표로 하는 구조물까지 진 입을 위해 자입점이 더 멀리 위치해야 하며, 칩습의 정도가 더 크다는 단점 또한 존재한다 49) . Out-of-plane의 경우 좁은 구 조물에서 시행하기에 용이하나, 바늘 끝을 찾기 어렵다는 단점 이 있다.…”
Section: 초음파 빔이 구성하는 평면과 자입 도구의 배치에 따라 장축 (Long Axis)으로 자입하는 방식을 In-p...unclassified
“…이 경우 전체 바늘의 위치를 시각화 하면서 관찰할 수 있으며, Out-of-plane의 경우 탐촉 자의 장축 방향과 바늘이 수직 방향이기에 바늘이 단면, 즉 점 (Dot)으로 보이게 된다 48) . 때문에 In-plane approach의 경우 바늘의 시각화에는 장점이 있지만, 목표로 하는 구조물까지 진 입을 위해 자입점이 더 멀리 위치해야 하며, 칩습의 정도가 더 크다는 단점 또한 존재한다 49) . Out-of-plane의 경우 좁은 구 조물에서 시행하기에 용이하나, 바늘 끝을 찾기 어렵다는 단점 이 있다.…”
Section: 초음파 빔이 구성하는 평면과 자입 도구의 배치에 따라 장축 (Long Axis)으로 자입하는 방식을 In-p...unclassified
“…We would like to congratulate the team of Dr Geannette for their retrospective analysis of cases undergoing ultrasound-guided injection to the biceps tendon sheath. 1 In the study, the authors found that 43% of the patients had a normal ultrasound appearance of the biceps tendon, followed by 36.6% with biceps tendinosis. A more interesting finding was that the ultrasound presentation of the biceps tendon was normal in half of the participants who reported postinjection pain relief.…”
mentioning
confidence: 94%